Pengaruh Kualitas Layanan, Kompetensi & Promosi Terhadap Citra Program Magister Manajemen Di Malang - Andri Firmansyah; Widji Astutik; Junianto Tjahjo Darsono (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2020)
This study aims to analyze the effect of service quality, competence, and promotion on the image of the Magister of Management Study program in Malang. The method used is quantitive research using a questionnaire research instrument that is distributed to master student in management. The Analysis used is multiple linear regression using SPSS. The results of this study indicate students’ perceptions of service quality, competence, and promotion effect the image of the master’s management study program and promotion becomes the dominant variable affecting the image of the master’s management study program.